Bride hard [videorecording (DVD)] - Steinberg, Shaina; Adams, CeCe Pleasants; Camp, Colleen, 1953-; Wilson, Rebel; Camp, Anna, 1982-; Chlumsky, Anna; Randolph, Da'Vine Joy, 1986-; Zumbado, Gigi, 1996-; Cola, Sherry, 1989-; Huntington, Sam, 1982-; O'Neill, Michael (Actor); Dorff, Stephen, 1973-; et al. (Magenta Light Studios, 2025)
"When a mercenary group takes a lavish wedding hostage, they have no idea what they are in for as the Maid of Honor is actually a secret agent ready to rain hell-fire upon anyone who would ruin her best friend's wedding."--